ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN ADMINISTRASI AKADEMIK PEGAWAI IAIN KENDARI - Sumianti Sumianti; Syamsuddin Syamsuddin; Sitti Nurhalimah; Hasbullah Hasbullah; Herlina Herlina; Musjuliana Musjuliana (Ta'dib, 2020)
Governance quality measurement of an educational institution is one of the main factors that can impact on the image of the college and the student loyalty. This article aims to describe and analyze the student satisfaction level of the academic administration services of IAIN Kendari staff. The research sample amounted to 88 students from 752 population numbers. The research instruments were structured using a service satisfaction indicator which refers to the tangible, reliability, responsiveness, assurance, and empathy aspects. The data were analyzed by using the Student Satisfaction Index analysis technique. The result of students’ satisfaction of academic agency activities was in satisfactory category. Besides, an interesting empirical finding in this research was the level of students’ satisfaction of the service positively correlates with the number of the employees. That is, the higher the number of employees, the higher the level of satisfaction of the service and vice versa. This indicates the need for the proportional distribution of academic administrative personnel in order to provide the more qualified academic service.